The MEDLINE Retriever. - Fowler, J. (American Medical Informatics Association, 1992)
Baylor College of Medicine has developed the MEDLINE Retriever, a tool to query MEDLINE, the data-base of medical literature at the National Library of Medicine. The MEDLINE Retriever communicates via the Internet to achieve excellent response time for MEDLINE queries. It uses the X Window System and the Motif toolkit, and employs the Knowbot Operating Environment developed by the Corporation for National Research Initiatives. We discuss the architecture of the MEDLINE Retriever, focusing on the graphical user interface that we have developed, as well as our experiences in developing and deploying the MEDLINE Retriever at Baylor. The MEDLINE Retriever is an extension of Baylor's IAIMS design concept that brought forth the Virtual Notebook System, and fits well with Baylor's aims with regard to the High Performance Computing Initiative.